2006
DOI: 10.1086/507919
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Methicillin-Resistant Staphylococcus aureus Colonization in a Surgical Intensive Care Unit

Abstract: of methicillin-resistant Staphylococcus aureus colonization in a surgical intensive care unit." Infection Control and Hospital Epidemiology. 27,10. 1032-1040. (2006 http://www.jstor.org/page/info/about/policies/terms.jsp JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 35 publications
(54 reference statements)
3
43
1
2
Order By: Relevance
“…Not surprisingly, these attributes are well known to be associated with a higher risk of HA-MRSA infection. [7][8][9]30 In addition, our study found that the proportion of admitted patients from lower socioeconomic backgrounds was also in-dependently predictive of a hospitals' proportion of HA-MRSA infections. The availability of resources in the home environment could influence the risk of HA infections that manifest in the immediate postdischarge period.…”
Section: Discussionsupporting
confidence: 50%
“…Not surprisingly, these attributes are well known to be associated with a higher risk of HA-MRSA infection. [7][8][9]30 In addition, our study found that the proportion of admitted patients from lower socioeconomic backgrounds was also in-dependently predictive of a hospitals' proportion of HA-MRSA infections. The availability of resources in the home environment could influence the risk of HA infections that manifest in the immediate postdischarge period.…”
Section: Discussionsupporting
confidence: 50%
“…However, the risk of acquiring an MDRO is likely increased with increased duration of prior hospitalization, previous antimicrobial exposure, and the rate of MDRO in the local environment. Epidemiologic studies of MRSA and ESBL Gram-negative colonization support this by demonstrating that colonization is associated with a prolonged hospital stay (25,26).…”
Section: Discussionmentioning
confidence: 92%
“…2,4 It is well recognized that nasal carriage of MRSA represents a major risk factor for subsequent infection and transmission of this pathogen. 5,6 Although several studies have reported the prevalence of MRSA nasal carriage in patients in health care-settings, 7,8 this subject has been little investigated in healthy individuals in the broader community, 9 and is practically unstudied in Brazil.…”
Section: Methicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%